2019
DOI: 10.1177/0309364618798172
|View full text |Cite
|
Sign up to set email alerts
|

Significance of recumbent curvature in prediction of in-orthosis correction for adolescent idiopathic scoliosis

Abstract: The curvature in recumbent positions (supine and prone) is highly correlated to the initial in-orthosis curvature without significant difference. Thus, the initial effect of spinal orthosis could be predicted by the curvature in the recumbent positions (especially prone position) at the pre-orthosis stage. Clinical relevance Prediction of in-orthosis correction at pre-orthosis stage is valuable for spinal orthosis design. This study suggests assessing the spinal curvature in recumbent position (especially pron… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(10 citation statements)
references
References 11 publications
0
9
1
Order By: Relevance
“…The patient's age at the beginning of brace treatment, Cobb angle, curve location, Risser stage, and in-brace correction are important factors for predicting treatment effectiveness in AIS. [26][27][28] In our study, although the mean of age was noticeably different between the progressed and nonprogressed groups at the beginning of brace treatment, there was no significant relationship between the prebrace age and brace effectiveness. This is consistent with the findings of Zhu et al 13 We found out that the prebrace Cobb angle in the nonprogressed group was significantly lower than the progressed group.…”
Section: Discussioncontrasting
confidence: 69%
“…The patient's age at the beginning of brace treatment, Cobb angle, curve location, Risser stage, and in-brace correction are important factors for predicting treatment effectiveness in AIS. [26][27][28] In our study, although the mean of age was noticeably different between the progressed and nonprogressed groups at the beginning of brace treatment, there was no significant relationship between the prebrace age and brace effectiveness. This is consistent with the findings of Zhu et al 13 We found out that the prebrace Cobb angle in the nonprogressed group was significantly lower than the progressed group.…”
Section: Discussioncontrasting
confidence: 69%
“…Table 2 shows the results of the QUIPS appraisal. Of the 14 articles included, five (59.4%) had a low risk of bias [ 6 , 14 , 15 , 28 , 29 ], three (21.4%) had a moderate risk [ 30 32 ], and the remaining six studies (42.9%) had a high risk of bias [ 16 , 17 , 33 36 ].…”
Section: Resultsmentioning
confidence: 99%
“…For six studies conducted by three research teams, AIS patients were prescribed an underarm thoraco-lumbo-sacral orthosis (TLSO) [ 6 , 14 , 16 , 29 , 30 , 36 ]. In another two studies from one team, a Hong Kong orthosis was prescribed [ 15 , 33 ]. The Providence nighttime brace was used in two other studies [ 31 , 32 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…For E1 (on the fours), the sEMG activity on the concave side increased more than the convex side and reached a symmetric sEMG activity on both sides. E1 may be regarded as a symmetric exercise with reduced longitudinal gravity on the spine, which would simultaneously correct the sagittal lordosis and coronal scoliosis of spinal deformity [ 20 ]. The symmetric sEMG activity of paraspinal muscles during E1 may be related to both the self-correction of the patients and the spontaneous correction by the postural change.…”
Section: Discussionmentioning
confidence: 99%